2014
DOI: 10.21608/jpp.2014.56520
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Foliar Spray With Seaweeds Extract and Chitozan on Earliness and Productivity of Globe Artichoke.

Abstract: Two field experiments were carried out during the two successive seasons of 2012/2013 and 2013/2014 at the Horticulture Research Farm of El-Bramoon, El-Dakahlia Governorate,, to investigate the response of globe artichoke plants cv. French, to foliar spray with seaweeds extract, chitozan levels and their combination on growth, earliness, quality, and productivity. The main results can be summarized as follows: 1). The results indicated that increasing seaweeds extract and chitozan levels individual or in combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
5
4
0
Order By: Relevance
“…The chemical and biochemical constituents of any seaweed extract act as biostimulants that work synergistically [55,56]. There was a good agreement with the results of previous studies that indicated the beneficial effects of diluted seaweed extracts on plants such as artichoke [15,42]. However, the study carried out by Canellas et al [57] concluded that humic acid was ineffective in improving vegetable crop nutrient uptake.…”
Section: Head Qualitysupporting
confidence: 71%
“…The chemical and biochemical constituents of any seaweed extract act as biostimulants that work synergistically [55,56]. There was a good agreement with the results of previous studies that indicated the beneficial effects of diluted seaweed extracts on plants such as artichoke [15,42]. However, the study carried out by Canellas et al [57] concluded that humic acid was ineffective in improving vegetable crop nutrient uptake.…”
Section: Head Qualitysupporting
confidence: 71%
“…The positive effects of seaweed extract in yield parameters could be due to the fact that it contains macro, micronutrients and amino acids that improve nutritional status, vegetative growth and yield. These results are in harmony with Saif-Eldeen et al (2014) who showed that the increasing seaweeds extract levels were accompanied with significant yield distribution (early, medium and late yields) compared with control. Also, Seaweed extract application for different crops has a great importance due to its content of organic matter, micro elements (Fe, Cu, Zn, Co, Mo, Mn and Ni), vitamins and amino acids.…”
Section: Yield and Its Componentssupporting
confidence: 90%
“…The positive effect of seaweeds extract on early yield characters was reported by Saif-Eldeen et al (2014) who showed that the high level of seaweeds extract were accompanied with significant yield distribution (early, medium and late yields) compared with control.…”
Section: Yield and Its Componentsmentioning
confidence: 63%
“…Saif Eldeen et al (2014) illustrated that receptacle contents of N, P, total sugars % and protein % of globe artichoke were greatly affected by chitosan treatments as compared to the control. Farouk and Abd El Mohsen (2011) showed that pronounce and highly significant increase in nitrogen, phosphorous and potassium percentages in the shoot due to exogenous application of chitosan (250 mg/l).…”
Section: Mineral Elementsmentioning
confidence: 99%